RAVIOLI VEGE SORGUM (RAVEGUM) SEBAGAI ONE DISH MEAL KONTINENTAL RENDAH GLUTEN - Mutiara Nugrahaeni, Aulia Nurizzah Rahmajati (Prosiding Pendidikan Teknik Boga Busana, 2020)
Sorghum (Sorghum spp.) Is one of the minor cereals that has future development prospects as food, feed and even as a substitute for wheat flour. Food use is consumed in the form of sorghum rice and sorghum flour in food diversification by local communities. High nutritional value and relatively low prices make sorghum as a high-carbohydrate food source to meet the nutritional needs of society. This provides an opportunity for the community to increase the use of sorghum flour as a functional food material such as making Ravioli Vege Sorgum (Ravegum). This study uses a type of 4D research, namely Define, Design, Develop and Disseminate. This Ravioli Vege Sorghum can be concluded that the product is worthy of being disseminated to the public from the results of taste, color, aroma, texture and overall results. Keywords: Ravioli, Sorghum, Sorghum Flour, Pasta